Assessment Of Safe Injection Practices in A Tertiary Care Hospital: A Cross-Sectional Study from Chhattisgarh - Divya Sahu; Narinder Gandhi (National Journal of Community Medicine, 2015)
Background: Unsafe injection practices are associated with transmis- sion of blood -borne pathogens. The present study was undertaken to determine the knowledge and practice about safe injection among injection providers in a tertiary care hospital.